The Relationship Of Family Support and Maternal Anxiety With Basic Immunization Compliance During The COVID-19 Pandemic: Basic Immunization Compliance - Nurdin Nurdin; Islaeli Islaeli; Ari Nofitasari; Wa Ode Rahmadania (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: To protect children from diseases that can be prevented by immunization during the COVID-19 pandemic, which is still serious, immunizations must still be completed on schedule. This study's goal was to determine how basic immunization compliance at the Angalomelai and Petoaha Villages in Kendari City related to maternal anxiety during the pandemic and family support. Methods: Descriptive-analytical research methods using a cross-sectional study design are used. Mothers with 72 children under five make up the population. The samples were determined based on the table by Krejci and Mogan and obtained as many as 63 respondents using the random sampling technique. Results: a p-value of 0.042 < 0.05 and a correlation coefficient value of 0.787, respectively, suggest a high positive correlation in both directions. A positive correlation direction with a very good correlation strength, with a p-value of 0.005 and a correlation coefficient of 0.994. Conclusion: there is a strong correlation between family support, maternal anxiety, and immunization compliance.